2014
DOI: 10.1371/journal.pcbi.1003846
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Size Dynamics as an Effectively Stochastic Process

Abstract: Long-term, repeated measurements of individual synaptic properties have revealed that synapses can undergo significant directed and spontaneous changes over time scales of minutes to weeks. These changes are presumably driven by a large number of activity-dependent and independent molecular processes, yet how these processes integrate to determine the totality of synaptic size remains unknown. Here we propose, as an alternative to detailed, mechanistic descriptions, a statistical approach to synaptic size dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
125
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(138 citation statements)
references
References 62 publications
(110 reference statements)
13
125
0
Order By: Relevance
“…One important property of biological networks that has raised much interest is their heterogeneous topology. Analyses of metabolic, protein interaction, gene regulatory and neural networks all show heterogeneous connectivity distributions, including heavy tails and modular structure [8][9][10][11][12][13][14]. Heterogeneous networks, such as those with a broad connectivity distribution, are generally more difficult to analyze; inferring their detailed topology requires exceedingly high statistics.…”
Section: Introductionmentioning
confidence: 99%
“…One important property of biological networks that has raised much interest is their heterogeneous topology. Analyses of metabolic, protein interaction, gene regulatory and neural networks all show heterogeneous connectivity distributions, including heavy tails and modular structure [8][9][10][11][12][13][14]. Heterogeneous networks, such as those with a broad connectivity distribution, are generally more difficult to analyze; inferring their detailed topology requires exceedingly high statistics.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments using time lapse imaging of dendritic spines have suggested that such distributions can arise from stochastic fluctuations that have a multiplicative component [3]. Another important finding is that the bigger and stronger synapses are more stable than the smaller and weaker ones [4,9,13]. This makes particularly strong synapses a good candidate for the anatomical substrate ofthose long-term memories which we may maintain for a lifetime.…”
Section: Stability Despite Constant Changementioning
confidence: 99%
“…Interestingly, foci generated with fast nucleation rate also tend to have a shorter lifetime 540 evidencing a saturating mechanism or self-regulation (compare [13]). Moreover, we used 541 our model to test the influence of the nucleation location of these foci.…”
mentioning
confidence: 99%
“…Experiments imaging the shape of dendritic spines can provide snapshots at 14 distinct time points, but mathematical models are needed to bridge between these time 15 points and to understand shape fluctuations and their properties. However, so far only 16 phenomenological models have been proposed [9,[12][13][14] that describe fluctuation 17 coarsely on a timescale of days. Here, we take a different approach by modelling the fast 18 actin dynamics underlying shape fluctuations.…”
mentioning
confidence: 99%
See 1 more Smart Citation